Effect of cobalt isomorphic substitution on the properties of goethite and the adsorption of lead - Liu, Xu; Xue, Wenlu; Zhang, Zijia; Zhou, Wei; Song, Shaoxian; Li, Yinta; Benzaazoua, Mostafa; Hu, Xiheng (Frontiers in Environmental Science, 2023)
Iron oxides are ubiquitous in the environment and often contain impurities because of their substitution by Al, Mn, Co, and other metals. However, few studies have focused on Co substitution and subsequent Pb(II) adsorption on its surfaces. Herein, the effect of the isomorphic substitution of Co on the physiochemical properties of goethite and the atomic-level mechanisms of lead sorption in relation to structural changes were investigated in this work. The results showed that Co substitution reduced the unit cell parameters and crystallinity of goethite. More Fe-OH groups on the surface were exposed with Co substitution, leading to the preferential sorption of Pb. The DFT calculations further revealed that the valence band was shortened and the total density of states was more biased towards the Fermi level in Co-substituted goethite, making the surface electrons more active. In addition, both Pb2+ and Pb(OH)+ were adsorbed by goethite, forming a tridentate complex with three oxygen atoms. In this process, sp3 hybridization mainly occurred. These results provide a new perspective for studying the properties of Co-substituted goethite and its reaction with lead, helping to expand the application of DFT calculations to simulate and predict the fixation and mobilization of heavy metals in goethite-rich soils/sediments.